Definiteness and Specificity in EFL - Castro-García, Damaris (2023)
This article explores the application of English parameter settings to mark specificity and definiteness by Costa Rican Spanish-speaking, L2 English young adults. A Forced Elicitation Task (FET) was used to analyze the participants’ choices. The data were analyzed in comparison to native speaker responses. The results show that these EFL learners find it particularly difficult to decide on the correct articles for specific nouns, even more so if they are indefinite NPs. Indefinite and definite non- specific NPs are assigned articles with less difficulty. The results point to the consideration of spaced learning practice in the context under study.